2016
DOI: 10.1159/000445114
|View full text |Cite
|
Sign up to set email alerts
|

Protein S100β in Late-Pregnancy Fetuses with Low Birth Weight and Abnormal Cerebroplacental Ratio

Abstract: Objective: To evaluate the umbilical cord venous S100β levels in late-pregnancy fetuses with abnormal growth and cerebral redistribution. Methods: The pulsatility index of the umbilical and middle cerebral arteries and the cerebroplacental ratio (CPR) were measured in 132 fetuses at ≥34 weeks, and the CPR was converted into multiples of the median (MoM). A blood sample from the umbilical vein was collected at birth, and the umbilical venous S100β levels were evaluated in small and non-small for gestational age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[6][7][8][9][10][11] Accordingly, improved detection of FGR has been identified as 1 of the top-10 interventions needed to reduce the global burden of stillbirth. 12 Although various tools are available to screen for FGR, including maternal obstetric history 13,14 and serum markers, [15][16][17][18][19][20][21] the most commonly screening approach is through sonographic fetal weight estimation to detect fetuses that are small for gestational age (SGA), defined empirically as an estimated fetal weight (EFW) <10th percentile for gestational age. [22][23][24][25][26] This approach, however, has a high false-positive rate for FGR, as the majority of SGA fetuses are healthy constitutionally small fetuses rather than growth restricted.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Accordingly, improved detection of FGR has been identified as 1 of the top-10 interventions needed to reduce the global burden of stillbirth. 12 Although various tools are available to screen for FGR, including maternal obstetric history 13,14 and serum markers, [15][16][17][18][19][20][21] the most commonly screening approach is through sonographic fetal weight estimation to detect fetuses that are small for gestational age (SGA), defined empirically as an estimated fetal weight (EFW) <10th percentile for gestational age. [22][23][24][25][26] This approach, however, has a high false-positive rate for FGR, as the majority of SGA fetuses are healthy constitutionally small fetuses rather than growth restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration in placental function during pregnancy results in compensatory hemodynamic changes in the fetus, with increased blood flow to the brain and other essential organs. This redistribution of cardiac output is typically seen in small‐for‐gestational‐age fetuses, or indeed, any fetus that fails to reach its growth potential regardless of gestation, and is associated with an increased risk of adverse perinatal and long‐term neurodevelopmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive production of S100β by glial cells may even lead to increased neuroinflammation and neurological dysfunction. Elevation of S100β was related to central nervous system injury (Yan et al, 2014) and poor outcome following brain injury (Morales-Rosello et al, 2017). In this study, the qRT-PCR results showed that the S100β mRNA level in the telencephalon was raised markedly in the fetal rats of the fatigue group.…”
Section: Discussionmentioning
confidence: 99%